A peridynamic approach to simulating fatigue crack propagation in composite materials. (9th January 2023) - Ni, Tao; Zaccariotto, Mirco; Galvanetto, Ugo
Abstract : In this article, a numerical tool is proposed in the framework of bond-based peridynamics to simulate fatigue crack propagation in composite materials and structures. The cycle-dependent damage-cumulative model derived from Peerlings' law and applied to a bilinear constitutive law is used to evaluate the fatigue degradation of the bond stiffness. Several benchmark cases are studied to validate the proposed approach. Finally, static and fatigue crack propagations in composite systems with single or multi-inclusions are simulated to illustrate the capabilities and characteristics of the developed approach. This article is part of the theme issue 'Ageing and durability of composite materials'.